Domestic Homicide in New Brunswick: An Overview of Some Contributing Factors - Doherty, Deborah (Atlantis, 2006)
This study looks at domestic homicides of women in New Brunswick from 1984 to 2005. It examines factors associated with higher homicide risk for women and reviews the criminal justice system response. The study suggests that national studies of domestic homicide are urban-centric and that rurality itself may be a risk factor.